Gideon Falls. Volume 1, The black barn - Lemire, Jeff (Image Comics, Inc., 2018)
The legend of the Black Barn tells of an otherwordly building that has appeared and reappeared throughout history, bringing death and madness in its wake. Now its mystery ensnares and entwines the lives of two very different men. One: a young recluse, obsessed with finding hidden clues within the city's trash. The other: a washed-up Catholic priest, finding his place in a small town that hides dark secrets. Neither of them are prepared for what's inside the Black Barn.